Pengaruh Kompetensi dan Krediblitas Pegawai terhadap Kinerja Pegawai Melalui Profesionalisme di Dinas Pekerjaan Umum dan Perumahaan Rakyat Provinsi Jambi - Permata, Vitta Loca; Bukit, Pantun; Sudirman, Sudirman (J-MAS (Jurnal Manajemen dan Sains), 2024)
The aim of this research is to obtain an overview of employee competence, credibility, professionalism and performance of Jambi Province PUPR Service employees. To find out and analyze the direct and indirect influence of employee competence and credibility on professionalism in the Jambi Province PUPR Service. To find out and analyze the direct and indirect influence of employee competence and credibility on employee performance at the Jambi Province PUPR Service. To find out and analyze the influence of professionalism on employee performance at the Jambi Province PUPR Service. To determine and analyze the influence of employee competence and credibility through professionalism on employee performance. The type of data obtained in this research uses quantitative data sourced from primary data obtained by conducting research and questionnaires, secondary data can be obtained by reading, studying and understanding. through other media sourced from literature and library books or data from agencies related to the researched. In this research, the object of research is the Jambi Province PUPR Service. Employee competency and credibility simultaneously and partially have a significant effect on employee professionalism at the Jambi Province PUPR Service. Employee competency and credibility simultaneously have a significant effect on the performance of Jambi Province PUPR Service employees. Professionalism partially has a significant effect on the performance of Jambi Province PUPR Service employees. Employee competence and credibility together have a significant effect on professionalism and performance.